การศึกษาการเปลี่ยนแปลงของตัวแปรในกระบวนการทำกิจกรรมอาสาของนักศึกษามหาวิทยาลัยเทคโนโลยีราชมงคลล้านนา - ศรีชัย (Pongsook Srichai) ปองสุข; ศุภฤกษ์ชัยสกุล(Numchai Supparerkchaisakul) นำชัย; จงวิศาล(Rattigorn Chongvisal) รัตติกรณ์ (Journal of Behavioral Science for Development, 2016)
(THE STUDY OF CHANGES IN VOLUNTEER ACTIVITY PROCESS VARIABLES OF RAJAMANGALA UNIVERSITY OF TECHNOLOGY LANNA STUDENTS) Abstract The purpose of this research was to study the changes of variables in volunteer process repeat over period of time. The sample was 152 first year students of Rajamangala University of Technology Lanna who were the member in volunteer club. The 311 members from multi-stage sampling method. Five questionnaires were used for 4 times data collecting. Descriptive statistics and latent growth curve model were used for data analyzing. This longitudinal study showed that: 1) The score of slope of volunteer motivation changed increasingly ,intercept and slope were related 2) The score of slope of social support was not change, intercept and slope were not related 3) The score of slope of volunteer behavior was not change, intercept and slope were related 4) The score of slope of volunteer satisfaction changed increasingly ,intercept and slope were related, and 5) The score of slope of attitude towards making social benefit contributions was not change, intercept and slope were related. Keyword: Volunteer Process Model, Latent Growth Curve Model